The Role of Technology in EFL Classroom with The Triple-E Framework - Laili Rahmatul Fajri (Program Studi Manajemen Pendidikan Islam, 2023)
This research undertaking aimed to investigate the role of technology in EFL Classroom at one of private college, in Tasikmalaya. This study is anchored on the Triple-E Framework of Liz Kolb which is a practical tool that measures the degree to which the technology in a lesson is helping students meet the learning goals. Respondents were asked on the effects of technology integration in the classroom based on the Dimensions of Triple-E Framework. Significant insights were also gained from the perceptions and responses from students regarding their exposure to technology tools as part of their learning process. The data from the survey yielded the diverse rankings of technology tools that were integrated in teaching methodologies. With a diverse frequency, technology is utilized in organizing text, images, audios, and videos through power point presentations in order to facilitate effective and efficient lecture and discussion for classroom interaction and enhancement. The data obtained from the survey identified the “Intermediate” Level of Literacy of the Integration of Information and technology tools. Among the ranking of tools that is commonly utilized were: laptop, DLP Projector, Smartphones while the most useful software were the Microsoft Office, Audios, Videos, Multimedia Players, Online Applications and resources as well as the Internet. The knowledge and skills in technology tool use determined in evaluation of the role of technology in achieving the learning objectives that aimed for the students which resulted among exceptional, strong and average connection. This study made an implication that the collaboration of in learning would help maximize and attain the learning objectives that could facilitate authentic development to the learners.